Financial benefits of an ISO 9001 certification - Ari Hróbjartsson 1983- (2012)
Several companies in Iceland have received ISO 9001 certification in recent years. It has been researched qualitatively whether there is a financial benefit from getting ISO 9001 certification in Iceland but it has never been researched quantitatively. In this research all ISO 9001 certified companies that were operating in a competitive market in Iceland were compared to similar companies in an effort to find out if there was a financial benefit from becoming ISO 9001 certified. The result of this research is that there is a significant positive difference between ISO 9001 certified companies in Iceland and companies without certification. The certified companies had a significant higher gross profit margins and return on sales ratio. There was also a difference in financial health of the certified companies from the non-certified companies where certified companies had lower debt ratio than companies that were not certified.